Supply Chains and Port Congestion Around the World - Komaromi, Andras (IMF Working Papers; Working Paper, 2022)
Rising prices and reports of empty shelves in major economies have drawn attention to the functioning of supply chains that normally operate smoothly in the background. Among the issues, the long delays that port congestion may have caused in delivering goods to consumers and firms have been gathering increasing attention. We shed light on these issues leveraging a unique data set on maritime transport. Two main features emerge. First, at the world level, we find that shipping times jumped upwards as soon as the COVID crisis hit, and after a marked acceleration from end-2020, delays surpassed 1.5 days on average by December 2021 - or roughly a 25 percent increase in global travel times. The estimated additional days in transit for the average shipment in December 2021 can be compared to an ad-valorem tariff of 0.9 to 3.1 percent. The midpoint of this range is approximately equal, in absolute value, to the global applied tariff reduction achieved over the 14-year period from 2003 to 2017. Second, not all congestion appears related to increased demand. Many ports, especially since mid-2021, exhibit longer wait times despite handling less cargo than pre-pandemic. Infrastructure upgrading is therefore likely a necessary, but not sufficient condition for building resilience during a crisis where other factors (such as labor shortages) may also become binding.